PENGARUH EMOSIONAL, KEMUDAHAN DAN PENGALAMAN PELANGGAN TERHADAP KEPUASAN PELANGGAN DI RUMAH MAKAN DI KOTA SURAKARTA - Ahmad, Sidiq (STIE Atma Bhakti, 2022)
Thepurposeofthisstudywastoexaminetheemotionaleffect.The convenienceand customerexperienceofrestoranSurakarta'scustomersatisfaction.Thepopulationin this studywere allcustomersofrestoranSurakartacitywithatotalsample of100people.The dataanalysismethodused includesthe analysisofresearch instrumentsconsistingof validity tests, reliability tests, classical assumption tests, and hypothesis testing. The resultsofthisstudy partially showthatemotionalcharacteristics haveapositive and significanteffectoncustomersatisfactionatrestoraninSurakartacity ,convenience hasa positiveand significanteffect on customer satisfaction at restoran inSurakarta City, customerexperience hasapositive andsignificanteffectoncustomersatisfactionat restoran Surakartacity.